An integrated risk management using Business Model Canvas: designing business model options for The Royal Malaysian Air Force in the digital era - Wan Abd Samad, Wan Abdullah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
The risk management becomes an important element in the organizations especially corporate organisation and it becomes a requirement to an organization if they want to expand their business to global. The risk management is important to the Royal Malaysian Air Force (RMAF) to show its readiness in facing up various risk. The RMAF responsibility is to safeguarding and protecting the dignity and sovereignty of Malaysian Airspace. In order to maintain airspace security, RMAF needs to identify the potential risk that can affect national security. The current risk management is good however, it still has a room for some improvement. The risk management is very important to help the RMAF to do preparation and mitigation according to the risks that have been identified. Every country has its own quality standard but mostly they are referring to the ISO concept. The aims of this study are to explore the knowledge on the risk management, to comparative study and to formulate a business model for The Future RMAF using Business Model Canvas (BMC) framework to assist identifying the strategic assets of the future RMAF. Thus, building a more effective and relevant Risk Management System. This review paper is based on secondary data in order to do the comparison and get the ideas to enhance RMAF Risk Management.